Torque estimator using MPPT method for wind turbines - Youssef Baala; Seddik Bri (International Journal of Electrical and Computer Engineering (IJECE), 2020)
In this work, we presents a control scheme of the interface of a grid connected Variable Speed Wind Energy Generation System based on Doubly Fed Induction Generator (DFIG). The vectorial strategy for oriented stator flux GADA has been developed To extract the maximum power MPPT from the wind turbine. It uses a second order sliding mode controller and Kalman observer, using the super twisting algorithm. The simulation describes the effectiveness of the control strategy adopted.For A step and random profiles of the wind speed, reveals better tracking and perfect convergence of electromagnetic torque and concellation of reactive power to the stator. This control limits the mechanical stress on the tansmission shaft, improves the quality of the currents generated on the grid and optimizes the efficiency of the conversion chain.